Effect of thermally expandable particle additives on the mechanical and reversibility performance of adhesive joints - Giulio Piazza; Matthew Burczyk; Marco Gerini-Romagnoli; Giovanni Belingardi; Sayed A. Nassar (Journal of Advanced Joining Processes, 2022)
This paper provides an experimental investigation of the effect of Thermally Expandable Particle (TEP) adhesive additive on the mechanical and reversibility performance of epoxy-bonded load single lap joints (SLJs). Joint substrates are made of aluminum 6061 and woven carbon fiber reinforced plastic 0/90/0 substrates. TEP additive is used for modifying the structural epoxy adhesive used in this study. An electrically charged RF coil is placed around the joint bond area; generated electromagnetic field would heat the aluminum substrate which would in turn heat the modified adhesive. Very large volumetric expansion of the hollow spherical Thermally Expandable Particles (TEPs) would significantly reduce adhesive strength and lead to joint debonding under a minimal load of 100 N. Various weight concentrations of the TEP in the range of 5% to 25% with particulate size from 6 to 16 µm are used for investigating the effect on joint static and fatigue strength as well as the reversibility performance. Measured time to achieve full debonding of the joint (under charged RF coil), is used for assessing the reversibility performance.